Comparing Younger and Older Adult Eyewitnesses: Examining the Simultaneous, Elimination, and Wildcard Lineup Procedures. Issue 1 (2nd January 2018) - Pica, Emily; Pozzulo, Joanna
Abstract : Older adults (60- to 99-year-olds) and younger adults (18- to 49-year-olds) viewed a videotaped theft and were then asked to provide a description of the perpetrator. Following a brief delay, participants were presented with a simultaneous, elimination, or wildcard lineup procedure that was either target-present or target-absent. Overall, younger adult eyewitnesses were more likely to be correct in their identification decisions, reported more perpetrator descriptors, and had a higher proportion of accurate descriptors compared to older adults. Moreover, the simultaneous and elimination procedures were superior to the wildcard procedure in target-absent lineups. When presented with a target-present lineup, participants were more likely to be correct when presented with the simultaneous procedure compared to the elimination procedure. Neither of the identification procedures that have been shown to be beneficial with child eyewitnesses appear to have influenced the rate of correct identification or correct rejection for older adults as a separate age group.